1971
DOI: 10.1007/bf01977277
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to benomyl and some chemically related compounds in strains of Penicillium species

Abstract: Two Penicillium species, viz P. brevicompaetum and P. corymbiferum, were isolated from senescent petioles of cyclamen and from bulbs of lilies, respectively, both samples treated previously with benomyl. The isolates turned out to be very resistant to this fungicide when grown on malt agar, supplied with the fungicide; at a concentration of 2000 ~zg/ml they were less inhibited than randomly chosen isolates of the same species on agar with 1 tzg/ml.The strains retained their resistance at the same level for at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Statistical analysis showed that this difference is significant. A similar curve, although less pronounced, was obtained by Bollen(1971) for a benomyl-tolerant strain of Penicillium brevicompactum. Because the fungus had a strong tendency to grow superficially on agar supplied with high concentrations of benomyl, it could be argued that the tolerance found in vitro might be due at least partially to a poor diffusion of MBC in the agar.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Statistical analysis showed that this difference is significant. A similar curve, although less pronounced, was obtained by Bollen(1971) for a benomyl-tolerant strain of Penicillium brevicompactum. Because the fungus had a strong tendency to grow superficially on agar supplied with high concentrations of benomyl, it could be argued that the tolerance found in vitro might be due at least partially to a poor diffusion of MBC in the agar.…”
Section: Resultssupporting
confidence: 69%
“…Compared with other pathogenic fungi, e.g. Botrytis cinerea (Bollen and Scholten, 1971), Cercospora arachidicola (Littrell, 1974), and Penicillium species (Bollen, 1971), this maximum tolerated dose is rather high, although not exceptionally so. This tolerance was repeatedly found in about 40 isolates over a period of four years.…”
Section: Resultsmentioning
confidence: 98%
“…These isolates were not cross-resistant to benomyl. In P. brevicompaetum and P. eorymbiferum both benomyl-resistant isolates of each species tested were resistant at the same level (Bollen, 1971). Jarvis and Hargreaves (1973) reported that all isolates of Botrytis cinerea obtained from raspberry and strawberry, where standard benomyl sprays did not control grey mold, grew immediately on 1000 ~g/ml benomyl agar.…”
Section: Discussionmentioning
confidence: 98%
“…She found that amounts of 0.15 to 0.60 kg ha-1 left most rhizosphere and root-colonizing fungi unaffected, but that the Penicillium population was markedly increased in treated plots. The increase in these sensitive fungi might have been due to development of resistance, as has been reported for some species of this genus (Bollen, 1971;Kuramoto, 1976). In contrast to their frequent occurrence on wheat roots in Weber-Czerwifiska's plots, penicillia were rare on roots of rye in our plots.…”
Section: Discussionmentioning
confidence: 90%